(untitled) (Asia Pacific Journal of Social Innovation, 2024)
This paper showcases two Intel Teach portfolios entitled Maranao Craft and Mathematics and Math Meets Music. Computers and graphics calculators are the tools used in designing interactive activities in the class. With technology. the students expand their creativity in applying content in mathematics. Under the project, students () made generalizations on the effects of the graph and applied translation concepts in graphing functions such as linear, polynomial, exponential, logarithmic and trigonometric functions: (2) wrote journals on their learning experiences and on how to relate mathematics to the real world: and (3) worked collaboratively to present results of research work through a multimedia presentation. Their journals and multimedia presentations were evaluated using rubrics. In Math Meets Music unit plan, students realized mathemnatics concepts behind diferent musical instruments as shown in their journals and multimedia projects. Technologyenhanced unit plans connect mathematics to other disciplines such as arts, research, history, culture, and music. Integrating technology in the classroom then ensures the best teaching and learning experience.